MiReCOL – A Handbook and Web Tool of Remediation and Corrective Actions for CO2 Storage Sites. (July 2017) - Brunner, Logan; Neele, Filip
Abstract: The use of CO2 storage for carbon emission reduction is crucial to achieve climate change goals. This can be seen through the efforts governments and organizations are putting on carbon capture and storage (CCS), such as at the recent climate talks in Paris (COP21) and reports from the International Panel on Climate Change (IPCC). Along with the push for CCS comes the requirement to ensure the safe and secure implementation of underground CO2 storage in order to gather support from governments and the public. The Mitigation and Remediation of CO2 Leakage (MiReCOL) project is designed to address this issue. MiReCOL is intended for CO2 storage operators and regulators and provides analyses of mitigation and remediation techniques against various leakage mechanisms. The analyses include computer simulation, laboratory tests, and field tests in Ketzin, Germany, Bečej, Serbia and K12-B, The Netherlands and cover both new and existing mitigation techniques. The project culminates with the compilation of a handbook of corrective measures and web tool, which will serve as a resource for operators and regulators. The handbook and web tool will be based off of the research conducted on the leakage mitigation techniques and the results obtained.